Aphasia of The Main Character in Documentary Movie My Beautiful Broken Brain - Adelia Ilahude; Rahman Taufiqrianto Dako; Nurlaila Husain (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The symptoms of aphasia will vary depending on the type of aphasia. This study examined symptoms to determine the type of aphasia. Qualitative data collection involved observation and documentation. This investigation found that the main character's Broca's aphasia is the most dominant. There are 5 of the 7 symptoms that happened in Lotje's case. The most common symptom is non-fluent (55 data), followed by naming (15 data), agrammatism (10 data), and phonological literal paraphasia and verbal paraphasias (3 data). This study suggests that reading about aphasia can help readers communicate with persons who have it.